An Analysis of Execution of Employee Compensation In Indonesia Post Company - Febiola, Mawar; Melandari, Nia; Farhan, Farhan; Ramadhan, Nazmi (CNPLUS Publisher, 2025)
This study is to find out the form of compensation and to find out more about the purpose of providing compensation to employees of PT Pos Indonesia Sentosa Raya Branch and to find out the obstacles that occur in the company in providing compensation to employees. The report on the results of the PBL compensation with the title